Hydrodynamic forces on submerged floating tube: The effect of curvature radius and depth level - Jamiatul Akmal; Asnawi Lubis; Ahmad Su'udi; Novri Tanti; Nurcahya Nugraha; Zaky Abyan Fahrain; Panji Firmanul Hakim (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2022)
The discussion of hydrodynamic forces becomes an important issue in determining the dynamic behaviour of the Submerged Floating Tunnel Bridge (SFTB) structure. As stated in the Morison Equation, the hydrodynamic forces are affected by the kinematics of water particles, but up to this date, there are only a few discussions for curved tube applications. This paper discusses the effect of curvature radius and depth level on hydrodynamic forces to get the correction factor for a straight tube. Tubes with variations in radius curvature (R/L) and diameter (D) were installed in a wave pool with a depth level (z/d). The hydrodynamic forces were detected by a load cell sensor placed on a pedestal at the end of the specimen. The data from the load cell was processed by the data acquisition system and displayed on the monitor screen, showing that the z/d ratio and the R/L ratio both affect the hydrodynamic forces. A larger z/d ratio (deeper) results in smaller hydrodynamic forces, while a smaller R/L ratio (more curved) results in smaller hydrodynamic forces. A correction factor (C) has been determined to calculate the hydrodynamic force on a curved tube based on the Morison equation.